Traditional knowledge applied to hunting and breeding of the vulnerable Yellow-footed Tortoise (Chelonoidis denticulatus) in the Cazumbá-Iracema Extractive Reserve, Acre, Brazil - Oliveira, Marcela Álvares; Costa-Rodrigues, Ana Paula Vitoria; Muniz Calouro, Armando (Ethnobiology and Conservation, 2022)
Hunting is intensely practiced in the Amazon and is related to the survival of riverside communities as a source of income and food. This study was conducted at Resex Cazumbá-Iracema between June and November, in the dry season and the beginning of the flood period. Twenty-one families were monitored, six hunting events were followed, and 23 C. denticulatus individuals were recorded, all of which were categorized as opportunistic. Among the studied individuals, 11 were males and 12 females, and those with a carapace over 40 cm were considered adults. The tortoise is captured mainly for food, but there are beliefs concerning its medicinal use in treating inflammatory  diseases. Reptiles, in general, are among the least hunted species for food in the Amazon. This preference may be related to the higher mammals’ biomass and the birds’ species richness. However, its importance for consumption may vary according to the location.